Cardiac pericytes function as key vasoactive cells to regulate homeostasis and disease - Lee, Linda L. (FEBS Open Bio, 2020)
Pericytes (PCs)—mural cells that envelop endothelial cells (ECs) of microvessels—regulate tissue‐specific vasculature development as well as maturation and maintenance of endothelial barrier integrity. However, little is known about their tissue‐specific function in the heart. Specifically, the mechanism by which cardiac PCs constrict coronary capillaries remains undetermined. To gain insights into the function of cardiac PCs at the cellular level, we isolated NG2(+) PDGFRβ(+) CD146(+) CD34(−) CD31(−) CD45(−) PCs for detailed characterization. Functionally, we provide evidence that these PCs increased transepithelial electrical resistance and decreased endothelial permeability. We show for the first time that this population of PCs express contractile proteins, are stimulated by adrenergic signaling, and demonstrate stereotypical contraction and relaxation. Furthermore, we also studied for the first time, the PCs in in vitro models of disease. PCs in hypoxia activated the hypoxia‐inducible factor 1 alpha pathway, increased secretion of angiogenic factors, and caused cellular apoptosis. Supraphysiological levels of low‐density lipoprotein decreased PC proliferation and induced lipid droplet accumulation. Elevated glucose levels triggered a proinflammatory response. Taken together, our study characterizes cardiac PCs under in vitro disease conditions and supports the hypothesis that cardiac PCs are key vasoactive cells that can regulate blood flow in the heart.